Pemberdayaan Masyarakat melalui Pelatihan Budidaya Jamur Tiram di Desa Bandar Khalipah Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Sumatera Utara - Nasution, Irda Wahidah; Nasution, Nurul Hidayah (Society : Jurnal Pengabdian Masyarakat, 2024)
Mushroom mushrooms, besides having a delicious taste, even similar to chicken meat, also have a nutritious content that is quite beneficial, so today they are a choice for the community as a food worth consuming. This makes the market demand for peanut mushrooms increase, not only from home but also from abroad, which is still a huge opportunity. Besides other advantages, the cultivation method is easy, can be done all year round, and does not require large land. Mushroom mushrooms are quite environmentally tolerant and can be used as primary or secondary work. Dusun VIII Angsana in Bandar Khalipah Village is a village located in Deli Serdang district, North Sumatra. The village community of Bandar Khalipah has a wide variety of occupations to fulfill everyday life, but his wives are mostly ordinary housewives. The method used is to enhance the knowledge and skills of household mothers in the family environment. Household mothers are representatives of the community who can use their free time for useful activities. The population profile in this area is appropriate for acquiring additional knowledge and skills that are useful for improving the quality of life and can also boost the economy. The target is the 8th Angsana Municipality of Bandar Khalipah, which has a total of 30 people composed of different household mothers. These households are expected to be stakeholders who can spread information to other members of the community. The procedure for the implementation of dedication to the community consists of three stages, including a survey and interview, preparation, and execution. Implementation of the program consists of several interactive activities from the beginning of the training activities in the form of tutorials presented in the room as well as practical activities followed by the partner members in the form of practices carried out outside the meeting room. The goal of this program is to continue the consistent mushroom-based culinary endeavors, so that will help the community to be able to engage directly or indirectly in the whole of the mushrooms. Through the various mushmo kulinery endeavors, it is expected to strengthen in the cultivation of fungus that, in the long term, will be very beneficial to all parties, the nature will be sustainable, including the society, and macro will be upgraded in his life. When the mindfulness of fungi can be an excellent product in the village of Bandar Khalipah, then consumers will come not only to travel but also to cook